Movement-based mind-body practices and cognitive function in middle-aged and older adults: Findings from the Midlife in the United States (MIDUS) study - Kallol Kumar Bhattacharyya; Gizem Hueluer; Hongdao Meng; Kathryn Hyer (Elsevier, 2021)
Objectives: Cognitive function is a key component of healthy aging. While conventional physical activities (walking, jogging, etc.) have been shown to support physical and cognitive health in late-life, it remains unclear whether traditional Eastern movement-based mind-body practices (MBP) have long-term cognitive benefits above and beyond conventional leisure physical activities. This study examines the relationship between movement-based MBP and cognitive function in middle-aged and older adults during a 10-year follow-up period. Methods: We used data from Waves 2 (2004−05) and 3 (2013−14) of the Midlife in the United States (MIDUS) study. MIDUS initially surveyed a national probability sample of community-living adults aged 24-75 years in 1995 (Wave 1). Tests of cognitive functioning measuring executive function and episodic memory were added in Wave 2 and repeated in Wave 3. We estimated multivariable linear regression models to examine the effect of MBP (Wave 2) on the episodic memory and executive function (Wave 3) while controlling for covariates (sociodemographic factors, health, and cognitive function at Wave 2). Results: A total of 2097 individuals aged 42-92 years (M = 64 ± 11, 56 % women) were included. After controlling for sociodemographic factors, health and functional status, and prior levels of cognitive function, engaging in MBP was independently associated with a smaller decline in episodic memory (b = 0.11, p = .03), but not executive function (b=0.03, p = .34). Discussion: The findings provide the first large population-based evidence supporting the cognitive benefits of MBP over a 10-year period among middle-aged and older adults. Future research should examine whether MBP are effective non-pharmacological intervention to attenuate age-related cognitive decline.